Syntheses of Atypically Fluorinated Peptidyl Macrocycles through Sequential Vinylic Substitutions. Issue 2 (20th November 2019) - Tsunemi, Tomoyuki; Bernardino, Salvador J.; Mendoza, Angel; Jones, Christopher G.; Harran, Patrick G.
Abstract: Small peptides containing combinations of cysteine, tyrosine, histidine, and serine residues react with octafluorocyclopentene (OFCP) to afford atypically structured macrocycles through successive vinylic substitutions. The reactions proceed rapidly in air at 0 °C and are tolerant of spectating tryptophan, asparagine, glutamine, and threonine residues. Hexapeptides of consensus sequence YXCXXC displace four fluorine atoms from OFCP to generate fluorinated macrobicyclic compounds that display dual‐turn surfaces. The method provides facile access to a wide range of previously unknown heterocyclic structures. Abstract : Synthetic peptides (red) containing combinations of Cys, Tyr, His, and Ser residues react rapidly with OFCP to afford atypically structured macrocycles through successive vinylic substitutions. YXCXXC sequences displace multiple fluorine atoms from OFCP to generate macropolycyclic compounds. This method provides facile access to a range of composite fluorinated macrocycles.